ISOLASI DAN IDENTIFIKASI RHIZOCTONIA MIKORIZA ANGGREK VANDATRICOLORDARI KOPENG JAWA TENGAH - Muhamad Zumri; DARYANTI DARYANTI; R. Soelistijono (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2017)
This study aims to identify mycorrhizal Rhizoctonia, morphology and anatomy, and determine the association of mycorrhizal Rhizoctonia among Vanda tricolor orchid from Kopeng Central Java with Vanda limbata from Malang, Jawa Timur. The research was held in June 2016 until December 2016 at Universitas Tunas Pembangunan Surakarta’s Laboratory. This research used direct observation by isolating the root of Vanda tricolor orchid and Vanda limbata orchid that has growth. The research stages are sampling, sterilization, isolation, purification, identification, data analysis. From the results of this study indicate: (1) there are no differences in mycorrhizal Rhizoctoniashape morphology and anatomy at the root of Vanda tricolor orchid and Vanda limbata orchid. (2) There is a peloton that is associated with the mycorrhizal Rhizoctonia on the roots of Vanda tricolor orchid and Vanda limbata orchid. (3) There are differences in the location of the peloton on the roots of Vanda tricolororchid and Vanda limbata orchid.